Correction: Constructing Benchmark Test Sets for Biological Sequence Analysis Using Independent Set Algorithms - Petti, Samantha; Eddy, Sean R (PLoS computational biology, 2023)
[This corrects the article DOI: 10.1371/journal.pcbi.1009492.].